Disc repositioning therapeutic exercise for disk anterior displacement with reduction in Temporomandibular joint - YODA, Tetsuya; ABE, Masato; SAKAMOTO, Ichiro; ONO, Toaki; TSUKAHARA, Hiroyasu; ENOMOTO, Shoji; MORITA, Shin; YODA, Yasushi (Journal of the Japanese Society for the Temporomandibular Joint, 1997)
Disc repositioning therapeutic exercise was performed for 117 patients with the click due to disk anterior displacement with reduction and with disk repositioning mandibular position. The effective rate was 47% and the mean duration of disapearance of click in the effective patients was 39.7±21.4 days. The effective rate of disc repositioning therapeutic exercise was compared about 9 items, including sex, age, presence or absence of pain, click period, timing of click, loudness of click, presence or absence of clenching, presence or absence of grinding of teeth, and presence or absence of eccentric mastication. The following 4 items were thought to be related to the outcomes of the therapy: 1. The effective rate (51.5%) in the the group aged 10 to 39 was higher than in the group aged 40 to 69 (26.3%). 2. The effective rate (54.2%) in the the group which the click period was 3 years or less was higher than the 3 yars or more group (29.4%). 3. The effective rate (58.3%) in the the group of the in early click was higher than middle click (47.1%) and late click (33.3%). 4. The effective rate (62.8%, 45.6%) in the the group of faintly touchable click and apparently touchable click was higher than audible click (11.8%).